Hesperia: The Journal of the American School of Classical Studies at Athens (JSTOR)
Hesperia is published quarterly by the American School of Classical Studies at Athens. Founded in 1932 and devoted primarily to the timely publication of reports on projects sponsored by the School, Hesperia also welcomes submissions from all scholars working in the fields of Greek archaeology, art, epigraphy, history, and literature. The geographic limits are those of the entire Greek world, with no chronological restrictions. Articles presenting primary research, interdisciplinary studies, theoretical discussions, and syntheses of topics and problems are all featured. Studies on the history and practice of archaeology and ethnography in the Mediterranean are also included. A 75-page limit currently exists for contributions. All submissions are refereed by at least two outside reviewers in a double-blind process. Articles accepted for publication appear roughly a year from the time of submission.
Keywords: Architecture & Architectural History